PEMBAHARUAN SISTEM EVALUASI DALAM SKALA MIKRO DAN SKALA MAKRO PADA PENGAJARAN BIOLOGI DI SMlJ - Bambang Subali, Bambang Subali (Jurnal Cakrawala Pendidikan, 2016)
The article discussed about the status and function of evaluation which is proportionally using both macro and Inicro scales on Biology"! specially in Senior High School. The discussion was applied by cOlTIbining theories and the facts exist. The result concluded that macro scale evaluation on Biology in Senior High School by using the natiasseSSlnent (Ebtanas) , which is only measuring the cognitive ability should be used as a mean to monitor and describe the quality of education in ilnproving the policy and not to deterlnine the graduation or entrance selection. The result of analysis on Ebtanas outcomes should be distributed to the teachers in order to make any improvement on teaching quality based on cognitive aspect. The graduation or student achievement on Biology related to the notion of IPA which contains the product and process skill was better to be assessed by using authentic assessment so that the students’ work could be the orientation of teaching-learning achievement.